Identiti Adalet ve Kalkinma Partisi (AKP) Turki di persimpangan: parti Islam atau sekular? - Wan Kamal Mujani,; Muhammad Khalis Ibrahim, (Penerbit Universiti Kebangsaan Malaysia, 2020)
The Adalet ve Kalkınma Partisi (AKP) which has a tendency towards Islam, but secular concurrently raises a question: what is the identity of the AKP? To date, this question is still being debated although generally, AKP has frequently been denoted as a party with an Islamic aspiration. Hence, this paper aims to revisit the identity of the AKP based on the framework of Islamic political movement. This paper fully adopted library research by examining sources related to the scope of the discussion. Ideologically, AKP makes conservative democracy as its ideology by harmonizing between conservative and liberal democratic values. The party also adheres to the secularism discourse although it meets almost all the characteristics of Islamic political movement for the Turkish context. Besides, it was found that the AKP has sided to religious interests in few issues. At the same time, AKP also has been resisted by military as the guardian of secular principle. This paper argues that the AKP is a party of its own identity, where it upholds the liberal version of secularism and tends to create an accommodative atmosphere for free religious practice. Finally, this paper offers some recommendations that can be considered for future studies.